Post-Socialist Urban Infrastructures (OPEN ACCESS) - Tuvikene, Tauri; Sgibnev, Wladimir; Neugebauer, Carola S. (Taylor & Francis, 2019)
Post-Socialist Urban Infrastructures critically elaborates on often forgotten, but some of the most essential, aspects of contemporary urban life, namely infrastructures, and links them to a discussion of post-socialist transformation. As the skeletons of cities, infrastructures capture the ways in which urban environments are assembled and urban lives unfold. Focusing on post-socialist cities, marked by neoliberalisation, polarisation and hybridity, this book offers new and enriching perspectives on urban infrastructures by centering on the often marginalised aspects of urban research-transport, green spaces, and water and heating provision. Featuring cases from West and East alike, the book covers examples from Azerbaijan, Bulgaria, Serbia, Croatia, Germany, Russia, Georgia, Lithuania, Poland, the Czech Republic, Tajikistan, and India. It provides original insights into the infrastructural back end of post-socialist cities for scholars, planners and activists interested in urban geography, cultural and social anthropology, and urban studies.